A review of the influences of organic farming on soil quality, crop productivity and produce quality. (21st July 2022) - Aulakh, Charanjit Singh; Sharma, Sandeep; Thakur, Manisha; Kaur, Parampreet
Abstract: Soil and crop management practices affect soil processes, agro-ecosystem functioning and sustainability of agricultural production systems. Organic farming production system is being promoted as a low cost environment friendly production system for, improved human and soil health, better environment, and increased agricultural sustainability. The reviewed literature is in consensus that organic farming, undoubtedly, improves soil quality due to application of organic manures and composts, and adoption of legume-based diversified cropping systems. Conversely, there is also consensus on lower productivity of crops (5–58%) under organic farming than the conventional system though exceptions are there. Despite the lower crop productivity, it may become more profitable if price premiums are available on organic produce. Its role in improving nutritional quality of produce though is debatable; but owing to absence of synthetic inputs organic produce is generally considered to be safer and healthy. The organic farming practices are expected to improve the soil quality over imbalanced and discriminate use of agro-chemical inputs. In sole productivity terms, organic farming may not be a viable farming system but in terms of overall ecosystem services, the system definitely has an edge over the conventional system.